Assessing the long-term economic impact of wheezing episodes after severe RSV disease in children from Argentina: a cost of illness analysis - Dvorkin, Julia; Pecenka, Clint; Sosa, Emiliano M; Sancilio, Andrea; Dueñas, Karina; Rodriguez, Andrea; Rojas-Roque, Carlos; Carruitero, Patricia B; Baral, Ranju; Vodicka, Elisabeth; Polack, Fernando P; Libster, Romina; et al. (BMJ public health, 2024)
IntroductionThere is lack of available data on the economic burden of wheezing episodes after severe respiratory syncytial virus (RSV) infection. This study aimed to assess the cost incurred for wheezing episodes after a severe RSV infection in children from Argentina, considering both the public health system and societal perspectives.MethodsA prospective cohort was conducted from 2014 to 2022 to assess the cost of illness of wheezing episodes after severe RSV disease in children from Buenos Aires, Argentina. Direct medical and non-medical costs were estimated, along with indirect costs per episode and patient. Data pertaining to healthcare resource utilisation, indirect expenses and parental out-of-pocket costs were obtained. The overall cost per hospitalisation and health visits was calculated. Costs were quantified in US dollars using the average exchange rate on the specific date of data collection.ResultsA total of 256 infants experienced severe RSV disease during their first year of life and were followed over a 5-year period in Buenos Aires. Overall, 150 children between 12 and 60 months presented 429 wheezing episodes. The median number of wheezing episodes per patient was 5 (IQR 3–7). The mean cost per wheezing episode was US$191.01 (95% CI 166.37 to 215.64). The total cost per episode of wheezing was significantly higher (p<0.001) in infants under 12 months of age (207.43, 95% CI 154.3 to 260.6) compared with older toddler. The average cumulative cost associated to wheezing per patient was US$415.99 (95% CI 313.35 to 518.63). Considering both acute RSV disease and long-term wheezing outcomes, the cumulative mean cost per patient was US$959.56 (95% CI 832.01 to 1087.10).ConclusionsThis study reveals the economic impact of prolonged wheezing resulting from severe acute RSV infection on Argentina’s public health system and society. The estimates obtained serve as valuable inputs for informing cost-effectiveness analyses of upcoming RSV preventive interventions.